Comparison of Turkish version of the medical outcomes study-HIV health survey with short form health survey-36 in people living with human immunodeficiency virus - TİGEN, ELİF; ÖZBEN SADIÇ, BESTE; KORTEN, VOLKAN; ERTÜRK ŞENGEL, BUKET (My University, 2022)
Background/aim Several questionnaires have been developed to evaluate the quality of life (QoL) for people living with human immunodeficiency virus (HIV). The aim of this study was to compare Turkish version of the Medical Outcomes Study-HIV Health Survey (MOS-HIV) with Short Form Health Survey (SF-36) in people with HIV. Patients and methods A hundred and 14 patients with HIV were consecutively included. The MOS-HIV and SF-36 questionnaires were applied to all patients at the same day. MOS HIV included 35 items and assessed general health perceptions (GH), physical functioning (PF), social functioning (SF), mental health (MH), bodily pain (P), cognitive functioning, health distress, overall QoL, health transition, role functioning (RF), energy/vitality (EV), physical (Physical health summary score) and mental (MHSS) health summary scores. SF-36 included 36 items and measured eight domains of health concepts including SF, PF, P, RF, GH, role emotional, vitality (V) and MH. Correlation analysis and Bland- Altman plots were used to compare the MOS-HIV and SF-36 questionnaires. Results GH, PF, P, RF, EV, SF, and MH domains of the MOS-HIV were significantly correlated with those of SF 36. The agreement between the tests were 91.2% for PF, 92.1% for RF and pain, 94.7% for GH, 95.6% for EV, 92.1% for SF and 93.9% for MH. Conclusion Turkish version of the MOS HIV showed moderate correlations and agreement with SF 36 suggesting its use as an alternative to SF 36 in assessing QoL in these patients.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Aile Hekimliği; Sosyal ve Beşeri Bilimler; Sosyoloji; Medicine; Health Sciences; Internal Medicine Sciences; Family Medicine; Social Sciences and Humanities; Sociology; SAĞLIK POLİTİKASI VE HİZMETLERİ; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); KAMU, ÇEVRE VE İŞ SAĞLIĞI; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; Klinik Tıp; Klinik Tıp (MED); HEALTH POLICY & SERVICES; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; HEALTH CARE SCIENCES & SERVICES; CLINICAL MEDICINE; Clinical Medicine (MED); Safety Research; General Social Sciences; Health (social science); Health Policy; Health Information Management; Leadership and Management; Review and Exam Preparation; Public Health, Environmental and Occupational Health; Medical Assisting and Transcription; Occupational Therapy; Medical Terminology; Community and Home Care; Epidemiology; Care Planning; Health Professions (miscellaneous); Social Sciences & Humanities; human immunodeficiency virus; medical outcomes study-HIV health survey; quality of life; QUALITY-OF-LIFE; MOS-HIV; RELIABILITY; VALIDITY; TRANSLATION; VALIDATION; HIV/AIDS; SF-36; human immunodeficiency virus; medical outcomes study–HIV health survey; quality of life